Limiting Vibroisolation Control of an Oscillating String on a Moving Base - Dmitry V. Balandin (Shock and Vibration)
The vibroisolating capability of an elastic object that is assumed to be protected against a class of excitations is studied. It is proposed that this capability be estimated by a quadratic functional. The solution method gives an estimate of the optimal isolation with a criterion of minimum guaranteed quality. A numerical example of the solution technique is presented.